How Important is Developmental Maturity in Assessing Whether Adolescents Will Share True or False Accounts of a First Offense in Legal Interactions? - Lavoie, Jennifer (Journal of developmental and life-course criminology, 2023)
We examined the developmental and situation-specific differences between four groupings of adolescents charged with a first offense: those who committed the crime and told the authorities they committed the crime (true confessors; 71%), those who committed the crime but told the authorities they did not commit the crime (false deniers; 8%), those who did not commit the crime but told the authorities they did commit the crime (false confessors; 12%) and those who did not commit the crime and told the authorities they did not commit the crime (true deniers; 10%). Findings indicate a developmental profile for each respondent grouping, and an overall effect in which adolescents with lower psychosocial maturity tended to have higher perceptions of the legitimacy and fairness of legal authorities. These results suggest that psychosocial maturity is an important factor to bear in mind even from the first legal interactions with officers of the justice system.